Habeas data e tutela jurisdicional da privacidade: aspectos processuais - Ribeiro, Sérgio Luiz de Almeida (2013)
This dissertation is about the habeas data and its procedural aspects, as a mean to protect privacy. The main objective of this study is to analyze the usefulness of this feature as a specific instrument for protection of individuals' privacy, as well as to ensure that citizens may control the wrongful use of their personal data through social networks and credit protection institutions. In this sense, the habeas data would not be restricted to obtaining general information or rectifying data before public authorities and private companies. In order to achieve this purpose, and based on the deductive method and bibliographical research, the following topics have been addressed in this paper: historical aspects, concept and objetive of the habeas data, proceedings upon habeas data under Law 9507/1997, and, lastly, controversial aspects on habeas data. As a conclusion, the main criticism developed herein is related to the comparison between the habeas data and the writ of mandamus, which has caused a procedural impact on the Law 9507/97. This Law, that rules the habeas data, changed the primary constitutional objective of it, which was very much related to the protection of privacy and the proceedings to achieve this objective. Another criticism that is addressed herein is related to the rule that imposes to the parties the burden of having an entire administrative process before making use of the habeas data to obtain information or rectify personal data. In theory, this rule refrains the habeas data to become an effective instrument for the avoidance of damages to individuals' privacy caused by credit protection institutions and social networks, for instance